Melukis Sebagai Media Pembentukan Kecerdasan Emosional Pada Remaja - Shokiyah, Nunuk Nur (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
Positive activities is necessary for teenagers to channel emotions, great . One of theactivities that can be selected is a credible form of painting . Some teens find it easier toexpress what is in themselves through graffiti , through activities such as painting .Painting is a positive activity for youth as an alternative activity to give him the freedomto express all emotions . This activity is very useful for young people to exerciseresponsibility and independence , which in turn is able to recognize her youth and theenvironment , in other words painting can foster emotional intelligence in adolescents.Emotional intelligence is the ability of individuals to recognize their emotions and theemotions of others and have the ability to channel his emotions appropriately , able tomotivate yourself , resilience in the face of failure , delay gratification and able to set themood . Painting could be interpreted as an expression of an expression of a statementof intent aimed feelings or thoughts or communicated to others . Feelings can becommunicated properly it will make teens become more in control of himself and theenvironment dengann able beriinteraksi good way.